Perancangan Mobile Learning dalam Mata Kuliah Bahasa Indonesia Berbasis Android - Dian Puspita; Leni Anggraeni; Widi Andewi (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
The beginning of 2020 is the year COVID-19 began to hit Indonesia. This is very influential for the world of education, where the Indonesian government makes the decision to do learning from home. This decision was made to reduce the spread of COVID-19 in school children and students, so that schools and colleges can learn from home, one of which is by using a mobile learning application. Mobile Learning is learning by using an android phone. This kind of learning is very effective in the current pandemic conditions. Because in addition to protecting students and students from COVID-19, both students and students still get subject matter or learning materials by staying at home. The system that built is a special learning system for Indonesian language courses, by presenting course material through applications that can be accessed by students without the constraints of a place to study.